2019
DOI: 10.1177/1071181319631428
|View full text |Cite
|
Sign up to set email alerts
|

Using a Situational Awareness Display to Improve Rider Trust and Comfort with an AV Taxi

Abstract: There is evidence that a significant portion of the population does not trust automated vehicles (AV). Research on trust in automation suggests that providing insight into how automation functions via a situational awareness (SA) display improves trust. However, it is unclear how much information is needed to build trust. A study was conducted to evaluate what amount of information improves passenger trust with an AV. After a ride in a simulated AV with one of four SA displays with varying amounts of informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The assistant system only showed a discomfort reduction during long THWs in the Braking scenarios. This means that the positive effect of transparent information indicated by the results of the studies by Chang et al (2019), Yang et al (2018) was only partly found for this system variation. However, in the post inquiry more than half of the participants rated the assistant system as very or extremely helpful in reducing their discomfort.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The assistant system only showed a discomfort reduction during long THWs in the Braking scenarios. This means that the positive effect of transparent information indicated by the results of the studies by Chang et al (2019), Yang et al (2018) was only partly found for this system variation. However, in the post inquiry more than half of the participants rated the assistant system as very or extremely helpful in reducing their discomfort.…”
Section: Discussionmentioning
confidence: 79%
“…It is possible that the displayed braking process of the driver was perceived rather like a warning or a highlighting of criticality in the situation increasing their discomfort. Another explanation could be that the braking information was displayed too late in the situation to have the same positive effect as the more predictive information about the intentions of an automated vehicle like in the study by Chang et al (2019) or Löcken et al (2016). The information displayed by the system was also rated as helpful in fewer situations compared to the other systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if fully-autonomous vehicles (level 5) do not need a driver, the awareness of the environment and the behavior of the car is considered as a confidence factor towards the system (also valid for the lower levels). It is therefore important to maintain the situation awareness in order to increase the trust of drivers towards these vehicles [25].…”
Section: Motivation and Objectivesmentioning
confidence: 99%